The potential of astronomy for socioeconomic development in Africa. (July 2018) - McBride, Vanessa; Venugopal, Ramasamy; Hoosain, Munira; Chingozha, Tawanda; Govender, Kevin
Since 2013, the International Astronomical Union's Office of Astronomy for Development has been funding and nurturing astronomy-for-development projects across the globe. In Africa, these projects aim to use astronomy to stimulate educational, technological and socioeconomic development.